Evaluation of the relationship between cytochrome P450 (CYP) 1A2 gene copy number variation and CYP1A2 protein content and enzyme activity in canine liver - Zamora, Francisco Gonzales; Bigelow, Hannah; Yang, Hong; Jimenez, Tania Perez (Frontiers in Veterinary Science, 2025)
Cytochrome P450 (CYP) 1A2 plays a key role in the metabolism of various drugs in dogs. However, the impact of genetic variation on differences in CYP1A2 metabolism among dogs remains unclear. Recent studies have identified variability in the copy number of the CYP1A2 gene, ranging from two to five copies. Additionally, a genetic polymorphism (stop codon) has been identified which results in the expression of an inactive protein, this has been investigated and changes in the pharmacokinetics of some clinically used drugs have been described. If these additional copies are functional, dogs with more CYP1A2 gene copies may exhibit faster drug clearance, potentially affecting appropriate drug dosing. To investigate this possibility, a well-characterized dog liver bank (N = 58) was analyzed to determine whether CYP1A2 copy number variation (CNV) correlates with CYP1A2 protein levels and enzyme activity. Real-time PCR was used to assess CYP1A2 CNV, while label-free mass spectrometry measured CYP1A2 protein concentration in liver microsomes. Theobromine N-3 demethylation was examined as a marker of canine CYP1A2 activity using commercially available recombinant CYPs and liver microsomes from dogs treated with isoform-selective enzyme inducers. Only CYP1A1 and CYP1A2 demonstrated the ability to catalyze theobromine N-3 demethylation, and this activity was induced exclusively by β-naphthoflavone. Liver microsome theobromine N-3 demethylation activity showed a moderate correlation with CYP1A2 protein levels (Rs = 0.46; p = 0.0003). Among the 58 liver samples genotyped for CYP1A2 CNV, nine dogs had two copies, 20 had three copies, 23 had four copies, and six had five copies. However, CYP1A2 CNV did not significantly correlate with CYP1A2 protein concentration (Rs = −0.14; p = 0.30) and showed a weak negative correlation with theobromine N-3 demethylation activity (Rs = −0.45; p = 0.00035). These findings suggest that CYP1A2 CNV is not a strong predictor of increased CYP1A2 protein expression or activity. According to the literature, CNV might not be relevant, but the genetic polymorphism (stop codon) could potentially be. The studies available show relationships between the stop codon and protein inactivity in the metabolizing of clinically used drugs. Further studies are necessary to validate these preliminary results.